Multicomponent organic blend systems: A review of quaternary organic photovoltaics - Kekeli N'Konou; Souk Y. Kim; Nutifafa Y. Doumon (Carbon Energy)
Abstract Embedding a third and/or fourth component into a binary blend active layer of organic photovoltaics (OPVs) is a promising approach to achieve high‐performance photovoltaic cells and modules. This multicomponent strategy favors absorption broadening via additional components. Quaternary OPV (QOPV) blends have four components in three possible configurations: (i) a donor and three acceptors, (ii) two donors and two acceptors, or (iii) three donors and an acceptor. Although quaternary systems have only been relatively recently studied compared to other systems in OPVs, leveraging the synergistic effects of the four components leads to record power conversion efficiencies, currently approaching 20%. QOPVs provide ample material choices for compatibility and channels for charge transfer mechanisms, possibly leading to optimized morphology and orientation. Reviewing recent progress in advancing QOPVs is essential for understanding their contribution to the OPV field. The review mainly discusses research progress in QOPVs with a keen interest in their various configurations, semitransparency, and outdoor and indoor applications. It describes the not‐well‐understood QOPV's general working mechanism. This review explores high‐performance QOPVs based on the fourth component's contribution as a donor, acceptor, or dye molecule and beyond in photovoltaic applications. Finally, there is a discussion around QOPV's outlook and projected future research directions in this field. This review intends to provide an overview of the quaternary systems approach to OPVs and inform current and future researchers on investigating the full spectrum of OPVs.